Akodon serrensis Thomas, 1902 (Mammalia: Rodentia: Sigmodontinae): records in Santa Catarina state, southern Brazil - André Testoni; Jaqueline Fumis; Sérgio Althoff; Fernando Tortato; Jorge Cherem (Check List, 2012)
We report Akodon serrensis Thomas, 1902 from three localities in the state of Santa Catarina, in southern Brazil. The specimens were identified based on cytogenetic and craniometric analyses. These are the first records of A. serrensis collected in Santa Catarina, which extend the range of this species ca. 330 km S.